2009
DOI: 10.1248/bpb.32.366
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functions of Bovine Milk-Derived .ALPHA.-Lactalbumin: Anti-nociceptive and Anti-inflammatory Activity Caused by Inhibiting Cyclooxygenase-2 and Phospholipase A2

Abstract: In recent years, milk constituents have become recognized as functional foods, suggesting that their use has a direct and measurable effect on health outcomes. Milk contains two primary sources of protein, the caseins and whey. After processing, the caseins are the proteins responsible for making curds, while whey remains in an aqueous environment. Whey has been touted as a functional food with a number of health benefits.1) The protein fraction in whey comprises four major protein fractions and six minor prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…We also reported anti-inflammatory and analgesic activity of α-lactoalbumin (10). Milk products are powerful acute stimulants of insulin secretion (11,12) and have the ability to enhance the insulin response when supplied in a mixed meal (13).…”
mentioning
confidence: 73%
“…We also reported anti-inflammatory and analgesic activity of α-lactoalbumin (10). Milk products are powerful acute stimulants of insulin secretion (11,12) and have the ability to enhance the insulin response when supplied in a mixed meal (13).…”
mentioning
confidence: 73%
“…We already reported that oral administered bovine milk-derived α-lactalbumin had anti-inflammatory activity inhibiting by COX-2. 16) Recently, it has been reported that dairy protein affect expression of PPARγ mRNA 24,25) From these results, α-lactalbumin suppressed adipose tissue inflammation and the ameliorating effects of α-lactalbumin on glucose intolerance in GK rats might be mostly caused by enhancement of adiponectin. In addition, α-lactalbumin might improve insulin sensitivity via enhancement of adiponection in peripheral tissues, but we have no data about glucose uptake in peripheral tissued or hepatic glycogenesis induced by insulin.…”
Section: Discussionmentioning
confidence: 97%
“…13) We have confirmed that lactoferrin protects tumor necrosis factor-α (TNF-α) production caused by sensitization of hepatic monocytes (kupffer cells) by lipopolisaccaride in C57BL/6J mice. 14) We also reported that oral administered bovine milk-derived α-lactalbumin (300 mg/kg) had anti-inflammatory 15) and anti-nociceptive activity by inhibiting cyclooxygenase-2 (COX-2) 16) in rat. The aim of the present study was to assess two points: 1) Can dietary treatment with α-lactalbumin improve impaired glucose tolerance?…”
mentioning
confidence: 99%
“…This complex may be considered as a potential therapeutic agent against various tumor cells [43,44]. Other authors [45] have demonstrated the anti-inflammatory activity of α-lactalbumin through the inhibition of cyclooxygenase-2 (COX-2) and phospholipase A 2 activities. Figure 4c shows the electropherogram for the donkey milk highmolecular-weight whey proteins separated by 2-DE (first dimension: IPG-strip pH 3-11, second dimension: 7.5% SDS-PAGE).…”
Section: Characterization Of Donkey Milk Protein Fraction By Twodimenmentioning
confidence: 99%